Water-Energy-Food Nexus in Arid Regions: A Bibliometric Review of Integrated Resource Management in Agriculture - Judijanto, Loso (Westscience Press, 2025)
This study conducts a bibliometric review of Water–Energy–Food (WEF) nexus research in arid and semi-arid agricultural systems from 2020 to 2025. Using data from Scopus and Web of Science, analyzed with VOSviewer and R-bibliometrix, 463 publications were mapped to identify key themes, collaborations, and research trends. Results show a rapid expansion of interdisciplinary studies focusing on sustainability, optimization, and climate resilience. Early research emphasized water management, while recent studies highlight renewable energy, agricultural productivity, carbon footprint reduction, and socio-economic governance. Leading contributors include Texas A&M University, University of KwaZulu-Natal, IHE Delft, and Hohai University, indicating strong transregional collaboration across Africa, Asia, and Europe. Thematically, the field is shifting toward integrated frameworks such as the WEFE nexus and circular bioeconomy approaches. The study concludes that the WEF nexus has become a crucial framework for achieving resource efficiency, climate adaptation, and food security in water-scarce environments. It offers theoretical advancement by linking systems governance with sustainability transitions and practical guidance for policymakers developing integrated resource strategies aligned with the SDGs.